Aryne Chemistry: Generation Methods and Reactions Incorporating Multiple Arynes - Kim, Nayoung; Choi, Myungsoo; Suh, Sung Eun; Chenoweth, David M. (Chemical Reviews, 2024)
Arynes hold significance for the efficient fusion of (hetero) arenes with diverse substrates, advancing the construction of complex molecular frameworks. Employing multiple equivalents of arynes is particularly effective in the rapid formation of polycyclic cores found in optoelectronic materials and bioactive compounds. However, the inherent reactivity of arynes often leads to side reactions, yielding unanticipated products and underlining the importance of a detailed investigation into the use of multiple arynes to fine-tune their reactivity. This review centers on methodologies and syntheses in organic reactions involving multiple arynes, categorizing based on mechanisms like cycloadditions, σ-bond insertions, nucleophilic additions, and ene reactions, and discusses aryne polymerization. The categorization based on these mechanisms includes two primary approaches: the first entails multiple aryne engagement within a single step while the second approach involves using a single equivalent of aryne sequentially across multiple steps, with both requiring strict reactivity control to ensure precise aryne participation in each respective step. Additionally, the review provides an in-depth analysis of the selection of aryne precursors, organized chronologically and by activation strategy, offering a comprehensive background that supports the main theme of multiple aryne utilization. The expectation remains that this comprehensive review will be invaluable in designing advanced syntheses engaging multiple arynes.
Keywords: Bioactive compounds; Bond insertion; Cycloadditions; Generation method; Generation reaction; Molecular frameworks; Nucleophilic additions; Optoelectronic materials; Organic reaction; Side reactions